Anti-radiation fabric and preparation method thereof
By reacting aamlated polyacrylonitrile with materials such as tetraaldehyde phenylporphyrin and boron hydroxynitride, functionalized polyacrylonitrile fibers are obtained, which solves the flame retardant and conductive properties of existing fabrics. The shortcomings of the fabric have achieved the improvement of the overall performance of the fabric and are suitable for a variety of complex application scenarios.
Patent Information
- Application Number
- CN202411625604.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing radiation-proof fabrics have shortcomings in flame retardant and conductive properties, and it is difficult to meet complex application needs at the same time, such as preventing radiation damage, preventing fires and eliminating electrostatic interference.
Porphyrin-based polyacrylonitrile was obtained by reacting amyotrol with tetraaldehyde phenylporphyrin and reacting with 3-(2-thienyl)-1-propylamine, combining hydroxyboron nitride with trimethoxy ( Thiophene-2-yl)silane was mixed with electrospin to produce functionalized polyacrylonitrile fibers, and after finishing, it was obtained with flame retardant and conductive properties.
It has achieved good flame retardant, conductive and radiation-proof properties of the fabric, and is suitable for protective clothing for medical personnel, military personnel and astronauts, expanding the application field of fabrics.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabrics, in particular to a radiation-proof fabric and a preparation method thereof. Background Art
[0002] With the development of science and technology and the improvement of people's safety awareness, the demand for radiation-proof fabrics is increasing, especially in the fields of medical, military, aerospace and electronics. Although the existing radiation-proof fabrics can prevent radiation damage to the human body to a certain extent, most of them have single functions and it is difficult to take into account the problems of flame retardancy and conductivity. This leads to the fact that under specific application conditions, such as the need to prevent radiation damage, prevent fire hazards and eliminate static interference at the same time, the existing fabrics are often difficult to meet the complex and changing use requirements.
[0003] Therefore, it is particularly necessary to develop a polyacrylonitrile fabric that can effectively block radiation and has flame retardant and conductive functions. The fabric prepared by the present invention not only provides the necessary radiation protection, but also expands the functionality of the fabric, has good flame retardancy and conductivity, and is very suitable for manufacturing protective clothing for medical personnel, equipment for military personnel, space suits for astronauts, and work clothes for electronic equipment operators. The development of this new type of radiation-proof fabric can provide users with more comprehensive protection and open up new application areas. Summary of the invention
[0004] The purpose of the present invention is to provide a radiation-proof fabric and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A radiation-proof fabric, comprising the following steps: reacting amino polyacrylonitrile with tetraaldehyde phenylporphyrin to obtain porphyrin-based polyacrylonitrile, reacting porphyrin-based polyacrylonitrile with 3-(2-thienyl)-1-propylamine to obtain thienyl polyacrylonitrile; reacting hydroxyboron nitride with trimethoxy(thien-2-yl)silane to obtain thienyl boron nitride; electrostatically spinning thienyl polyacrylonitrile and thienyl boron nitride to obtain functionalized polyacrylonitrile fibers; weaving the functionalized polyacrylonitrile fibers to obtain functionalized polyacrylonitrile fabrics; and finishing the functionalized polyacrylonitrile fabrics with 9,10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide and thiophene to obtain the radiation-proof fabrics.
[0006] A method for preparing a radiation-proof fabric comprises the following steps: (1) Aminated polyacrylonitrile, tetraaldehyde phenylporphyrin, trifluoroacetic acid and N,N-dimethylformamide are mixed uniformly in a mass ratio of 1:2-3:5-6:50-60, and vacuum-purged and nitrogen-purged for three cycles, with a vacuum degree of 80-100 Pa. In a nitrogen atmosphere, the temperature is raised to 110-120° C., and the reaction is stirred for 48-50 hours at a stirring speed of 300-400 r / min. After the stirring reaction is completed, an equal volume of dichloromethane and N,N-dimethylformamide are added, and the mixture is dried at 50-60° C. for 6-8 hours to obtain porphyrin-based polyacrylonitrile; (2) Thienyl polyacrylonitrile, 3-(2-thienyl)-1-propylamine, trifluoroacetic acid and N,N-dimethylformamide are mixed uniformly in a mass ratio of 1:3-4:5-6:50-60, and vacuum-purged and nitrogen-filled for three cycles, with a vacuum degree of 80-100 Pa. In a nitrogen atmosphere, the temperature is raised to 110-120° C., and the mixture is stirred for 48-50 hours at a stirring speed of 300-400 r / min. After the stirring reaction is completed, an equal volume of dichloromethane and N,N-dimethylformamide are added, and the mixture is dried at 50-60° C. for 6-8 hours to obtain thienyl polyacrylonitrile; (3) Mix hydroxyboron nitride, trimethoxy(thiophene-2-yl)silane and anhydrous ethanol in a mass ratio of 1:0.3-0.5:50-60, ultrasonicate at 20-40kHz for 10-20min, stir and react at room temperature for 2-3h at a stirring speed of 300-400r / min, filter and wash with anhydrous ethanol for 3-4 times, and dry in a vacuum drying oven at a temperature of 50-60°C and a vacuum degree of 0.08MPa for 10-12h to obtain thiophene boron nitride; (4) mixing thienyl boron nitride and N,N-dimethylformamide, ultrasonically treating at 20-40 kHz for 30-40 min, then sequentially adding thienyl polyacrylonitrile and anhydrous ferric chloride, stirring at room temperature for 20-30 min at a stirring speed of 400-600 r / min, and ultrasonically defoaming at 20-40 kHz for 30-40 min to obtain a spinning solution; (5) sucking the spinning solution with a syringe, squeezing the spinning solution out through a needle, the extruded spinning solution enters the coagulation liquid to obtain primary fibers, the primary fibers are sequentially subjected to a first mechanical drafting, a second mechanical drafting, a third mechanical drafting and a drafting box to obtain stretched fibers, and finally, the stretched fibers are collected on a winding roller to obtain functionalized polyacrylonitrile fibers, the functionalized polyacrylonitrile fibers are subjected to twisting, fixed twisting, warping, drawing in, and weaving on a machine to obtain fabrics, thereby obtaining functionalized polyacrylonitrile fabrics; (6) Prepare finishing agent 1 and finishing agent 2, immerse the functionalized polyacrylonitrile fabric in finishing agent 1 and let it stand for 2-3 minutes, finish it through a dipping and rolling process with a rolling rate of 80%, pre-dry it at a temperature of 140°C for 3 minutes, and then dry it at 100°C for 3 minutes, continue to immerse it in finishing agent 2, and then add anhydrous ferric chloride, let it stand for 2-3 minutes, finish it through a dipping and rolling process with a rolling rate of 80%, pre-dry it at a temperature of 40°C for 3 minutes, and then dry it at 100°C for 3 minutes, wash it with pure water for 5-6 times, and dry it at 50-60°C for 6-8 hours to obtain radiation-proof fabric.
[0007] As an optimization, the preparation method of the amino polyacrylonitrile in step (1) is to uniformly mix polyacrylonitrile, triethylenetetramine and N,N-dimethylformamide in a mass ratio of 1:8-12:15-20, and stir the mixture at 90-100°C for 4-6 hours. After the stirring, add dichloromethane in an amount of 20-30 times the mass of the polyacrylonitrile, filter and wash with ethanol for 3-4 times, and dry in a vacuum drying oven at a temperature of 80°C and a vacuum degree of 0.08 MPa for 12-14 hours to obtain the amino polyacrylonitrile.
[0008] As an optimization, the preparation method of hydroxyboron nitride in step (3) is to mix boron nitride and 5 mol / L sodium hydroxide aqueous solution in a mass ratio of 1:10-15, stir the reaction at 110-120°C for 10-12h, and the stirring speed is 200-300r / min. After cooling to room temperature, filtering and washing with pure water for 5-7 times, and drying in a vacuum drying oven at a temperature of 50-60°C and a vacuum degree of 0.08MPa for 10-12h to obtain hydroxyboron nitride.
[0009] As an optimization, the weighed amounts of thienyl boron nitride, N,N-dimethylformamide, thienyl polyacrylonitrile and anhydrous ferric chloride in step (4) are: by mass, 1-2 parts of thienyl boron nitride, 100-150 parts of N,N-dimethylformamide, 10-15 parts of thienyl polyacrylonitrile and 0.3-0.5 parts of anhydrous ferric chloride.
[0010] As an optimization, the syringe specification of step (5) is 20 mL, the inner diameter of the needle is 0.5 mm, the extrusion speed is 0.38-0.42 mL / min, the coagulation liquid is a mixture of N,N-dimethylformamide and water in a volume ratio of 1:1, the speed of the first stretching roller is 20 r / min, the speed of the second stretching roller is 32 r / min, the speed of the third stretching roller is 36 r / min, the temperature of the stretching box is 115°C, and the speed of the winding roller is 38 r / min.
[0011] As an optimization, the preparation method of the finishing agent 1 in step (6) is to mix 9,10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide and N,N-dimethylformamide at a mass ratio of 1:20-30, and the preparation method of the finishing agent 2 is to mix thiophene and tetrahydrofuran at a mass ratio of 1:20-30, and the addition amount of the anhydrous ferric chloride is 0.2-0.3 times the mass of thiophene.
[0012] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing the radiation-proof fabric, the present invention comprises the following steps: reacting amino polyacrylonitrile with tetraaldehyde phenylporphyrin to obtain porphyrin-based polyacrylonitrile, reacting porphyrin-based polyacrylonitrile with 3-(2-thienyl)-1-propylamine to obtain thienyl polyacrylonitrile; reacting hydroxyboron nitride with trimethoxy(thien-2-yl)silane to obtain thienyl boron nitride; electrostatic spinning of thienyl polyacrylonitrile and thienyl boron nitride to obtain functionalized polyacrylonitrile fiber; weaving the functionalized polyacrylonitrile fiber to obtain the functionalized polyacrylonitrile fabric, and finishing the functionalized polyacrylonitrile fabric with 9,10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide and thiophene to obtain the radiation-proof fabric.
[0013] First, amino polyacrylonitrile and tetraaldehyde phenylporphyrin are reacted to obtain porphyrin-based polyacrylonitrile, and tetraaldehyde phenylporphyrin is grafted with amino polyacrylonitrile through Schiff base reaction, and excess tetrahydroxyaldehyde phenylporphyrin makes porphyrin-based polyacrylonitrile carry aldehyde group, and then Schiff base reaction is carried out with 3-(2-thienyl)-1-propylamine to obtain thienyl polyacrylonitrile with thiophene, and the Schiff base structure contained in the thienyl polyacrylonitrile can be grafted with flame retardant through hydrogen phosphine reaction in the subsequent finishing process to give the fabric good flame retardant performance, the porphyrin structure can complex iron ions in the finishing process to give the fabric a certain thermal stability, and the thiophene structure can make the fabric have polythiophene structure in the process of co-blending electrospinning and finishing, and give the fabric good conductive performance; Secondly, hydroxy boron nitride and trimethoxy (thiophene-2-yl) silane are reacted to obtain thiophene boron nitride. Boron nitride is a kind of good thermal conductive radiation protection material, which can give the fabric good radiation protection performance. Hydroxylated boron nitride and trimethoxy (thiophene-2-yl) silane are coupled to make the boron nitride have a thiophene structure. The boron nitride with a thiophene structure and the thiophene-based polyacrylonitrile with a thiophene structure can be cross-linked when blended, thereby enhancing the mechanical properties of the fabric. In the process of post-finishing, the fabric has a polythiophene structure, which gives the fabric good conductive properties. Finally, the functionalized polyacrylonitrile fiber is spun and woven to obtain the functionalized polyacrylonitrile fabric, and then the functionalized polyacrylonitrile fabric is finished with thiophene and 9,10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide to obtain the radiation-proof fabric. The Schiff base structure on the functionalized polyacrylonitrile fabric can react with 9,10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide, thereby introducing a flame retardant structure on the fabric, thereby giving the fabric good flame retardant properties. The thiophene structure on the polyacrylonitrile fabric can form a larger polythiophene structure after finishing with thiophene monomer, thereby further improving the conductive properties of the polyacrylonitrile fabric. DETAILED DESCRIPTION
[0014] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0015] The boron nitride particles used in the following examples and comparative examples have a particle size of 1-2 μm and were purchased from Titan Technology. Example 1
[0016] A method for preparing a radiation-proof fabric, the method comprising the following steps: (1) Polyacrylonitrile, triethylenetetramine and N,N-dimethylformamide were mixed in a mass ratio of 1:8:15, stirred and reacted at 100°C for 6 hours, and after the stirring was completed, dichloromethane 20 times the mass of the polyacrylonitrile was added, filtered and washed with ethanol for 3 times, and dried in a vacuum drying oven at a temperature of 80°C and a vacuum degree of 0.08MPa for 12 hours to obtain amino polyacrylonitrile; amino polyacrylonitrile, tetraaldehyde phenylporphyrin, trifluoroacetic acid and N,N-dimethylformamide were mixed in a mass ratio of 1:2:5:50, and vacuum-purged and nitrogen-passed for three cycles at a vacuum degree of 100Pa. Under a nitrogen atmosphere, the temperature was raised to 120°C, stirred and reacted for 50 hours at a stirring speed of 400r / min. After the stirring reaction was completed, dichloromethane in an amount equal to that of N,N-dimethylformamide was added, and dried at 60°C for 8 hours to obtain porphyrin-based polyacrylonitrile; (2) Porphyrin-based polyacrylonitrile, 3-(2-thienyl)-1-propylamine, trifluoroacetic acid and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:3:5:50, and vacuum-purged and nitrogen-purged for three cycles with a vacuum degree of 80 Pa. Under a nitrogen atmosphere, the temperature was raised to 120°C, and the reaction was stirred for 50 hours at a stirring speed of 400 r / min. After the stirring reaction was completed, an equal volume of dichloromethane and N,N-dimethylformamide were added, and the mixture was dried at 60°C for 8 hours to obtain thienyl polyacrylonitrile; (3) Boron nitride and 5 mol / L sodium hydroxide aqueous solution were mixed in a mass volume ratio of 1:10, stirred and reacted at 120°C for 12 hours at a stirring speed of 300 r / min, and after cooling to room temperature, filtered and washed with pure water for 7 times, and dried in a vacuum drying oven at a temperature of 60°C and a vacuum degree of 0.08 MPa for 12 hours to obtain hydroxyboron nitride; hydroxyboron nitride, trimethoxy(thiophene-2-yl)silane, and anhydrous ethanol were mixed in a mass ratio of 1:0.3, ultrasonicated at 40 kHz for 20 minutes, stirred and reacted at room temperature for 3 hours at a stirring speed of 400 r / min, filtered and washed with anhydrous ethanol for 4 times, and dried in a vacuum drying oven at a temperature of 60°C and a vacuum degree of 0.08 MPa for 12 hours to obtain thienyl boron nitride; (4) Weigh 1 part of thienyl boron nitride, 100 parts of N,N-dimethylformamide, 10 parts of thienyl polyacrylonitrile, and 0.3 parts of anhydrous ferric chloride, by mass, mix the thienyl boron nitride and N,N-dimethylformamide, and ultrasonicate at 20 kHz for 40 min. Then, add thienyl polyacrylonitrile and anhydrous ferric chloride in sequence, stir at room temperature for 30 min at a stirring speed of 600 r / min, and ultrasonicate at 40 kHz for 40 min to obtain a spinning solution; (5) The spinning solution is sucked by a syringe, and the spinning solution is squeezed out through a needle. The extruded spinning solution enters a coagulation liquid to obtain a primary fiber. The primary fiber is sequentially subjected to a first mechanical drawing, a second mechanical drawing, a third mechanical drawing and a drawing box to obtain a stretched fiber. Finally, the stretched fiber is collected on a winding roller to obtain a functionalized polyacrylonitrile fiber. The syringe specification is 20 mL, the inner diameter of the needle is 0.5 mm, the extrusion speed is 0.38 mL / min, the coagulation liquid is a mixture of N,N-dimethylformamide and water in a volume ratio of 1:1, the speed of the first drawing roller is 20 r / min, the speed of the second drawing roller is 32 r / min, the speed of the third drawing roller is 36 r / min, the temperature of the drawing box is 115 ° C, and the speed of the winding roller is 38 r / min. The functionalized polyacrylonitrile fiber is twisted, fixed twisted, warped, drawn in, and woven into a fabric to obtain a functionalized polyacrylonitrile fabric. (6) 9,10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide and N,N-dimethylformamide were mixed in a mass ratio of 1:20 to obtain a finishing agent 1; thiophene and tetrahydrofuran were mixed in a mass ratio of 1:20 to obtain a finishing agent 2; the functionalized polyacrylonitrile fabric was immersed in the finishing agent 1 and allowed to stand for 2 minutes, and then finished by a dip-and-roll process with a rolling rate of 80%, pre-baked at a pre-baking temperature of 140°C and a pre-baking time of 3 minutes, and then dried at 100°C for 3 minutes, and continued to be immersed in the finishing agent 2, and then anhydrous ferric chloride 0.2 times the mass of thiophene was added, and allowed to stand for 2 minutes, and finished by a dip-and-roll process with a rolling rate of 80%, and then pre-baked at a pre-baking temperature of 40°C and a pre-baking time of 3 minutes, and then dried at 100°C for 3 minutes, and then washed with pure water 5 times, and dried at 60°C for 8 hours to obtain a radiation-proof fabric. Example 2
[0017] A method for preparing a radiation-proof fabric, the method comprising the following steps: (1) Polyacrylonitrile, triethylenetetramine and N,N-dimethylformamide were mixed evenly in a mass ratio of 1:10:17, stirred and reacted at 95°C for 5 hours, and after the stirring was completed, dichloromethane 25 times the mass of the polyacrylonitrile was added, filtered and washed with ethanol three times, and dried in a vacuum drying oven at a temperature of 80°C and a vacuum degree of 0.08MPa for 13 hours to obtain amino polyacrylonitrile; amino polyacrylonitrile, tetraaldehyde phenylporphyrin, trifluoroacetic acid and N,N-dimethylformamide were mixed evenly in a mass ratio of 1:2.5:5.5:55, and vacuumed and nitrogen-filled for three cycles at a vacuum degree of 90Pa. Under a nitrogen atmosphere, the temperature was raised to 115°C, stirred and reacted for 49 hours at a stirring speed of 350r / min. After the stirring reaction was completed, dichloromethane in an amount equal to that of N,N-dimethylformamide was added, and dried at 55°C for 7 hours to obtain porphyrin-based polyacrylonitrile; (2) Porphyrin-based polyacrylonitrile, 3-(2-thienyl)-1-propylamine, trifluoroacetic acid and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:3.5:5.5:55, and vacuum-purged and nitrogen-purged for three cycles with a vacuum degree of 90 Pa. The temperature was raised to 115°C in a nitrogen atmosphere, and the reaction was stirred for 49 hours at a stirring speed of 350 r / min. After the stirring reaction was completed, an equal volume of dichloromethane and N,N-dimethylformamide were added, and the mixture was dried at 55°C for 7 hours to obtain thienyl polyacrylonitrile; (3) Boron nitride and 5 mol / L sodium hydroxide aqueous solution were mixed in a mass volume ratio of 1:12, stirred at 115°C for 11 hours, and stirred at a speed of 250 r / min. After cooling to room temperature, the mixture was filtered and washed with pure water for 6 times, and dried in a vacuum drying oven at a temperature of 55°C and a vacuum degree of 0.08 MPa for 10 hours to obtain hydroxyboron nitride; (4) Hydroxyboron nitride, trimethoxy(thiophene-2-yl)silane, and anhydrous ethanol were mixed in a mass ratio of 1:0.5:55, ultrasonicated at 30 kHz for 15 minutes, stirred at room temperature for 2.5 hours, and stirred at a speed of 350 r / min. The mixture was filtered and washed with anhydrous ethanol for 3 times, and dried in a vacuum drying oven at a temperature of 55°C and a vacuum degree of 0.08 MPa for 10 hours to obtain thiophene boron nitride; (4) Weigh 1 part of thienyl boron nitride, 120 parts of N,N-dimethylformamide, 13 parts of thienyl polyacrylonitrile, and 0.4 parts of anhydrous ferric chloride, by mass, mix the thienyl boron nitride and N,N-dimethylformamide, and ultrasonicate at 30 kHz for 35 min. Then, add thienyl polyacrylonitrile and anhydrous ferric chloride in sequence, stir at room temperature for 25 min at a stirring speed of 500 r / min, and ultrasonicate at 30 kHz for 35 min to obtain a spinning solution; (5) The spinning solution is sucked by a syringe, and the spinning solution is squeezed out through a needle. The extruded spinning solution enters a coagulation liquid to obtain a primary fiber. The primary fiber is sequentially subjected to a first mechanical drawing, a second mechanical drawing, a third mechanical drawing and a drawing box to obtain a stretched fiber. Finally, the stretched fiber is collected on a winding roller to obtain a functionalized polyacrylonitrile fiber. The syringe specification is 20 mL, the inner diameter of the needle is 0.5 mm, the extrusion speed is 0.4 mL / min, the coagulation liquid is a mixture of N, N-dimethylformamide and water in a volume ratio of 1:1, the speed of the first drawing roller is 20 r / min, the speed of the second drawing roller is 32 r / min, the speed of the third drawing roller is 36 r / min, the temperature of the drawing box is 115 ° C, and the speed of the winding roller is 38 r / min. The functionalized polyacrylonitrile fiber is twisted, twisted, warped, drawn, and woven into a fabric to obtain a functionalized polyacrylonitrile fabric. (6) 9,10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide and N,N-dimethylformamide were mixed in a mass ratio of 1:25 to obtain a finishing agent 1; thiophene and tetrahydrofuran were mixed in a mass ratio of 1:25 to obtain a finishing agent 2; the functionalized polyacrylonitrile fabric was immersed in the finishing agent 1 and allowed to stand for 2 minutes, and then finished by a dip-and-roll process with a rolling rate of 80%, pre-baked at a pre-baking temperature of 140°C and a pre-baking time of 3 minutes, and then dried at 100°C for 3 minutes, and continued to be immersed in the finishing agent 2, and then anhydrous ferric chloride 0.25 times the mass of thiophene was added, and allowed to stand for 2 minutes, and finished by a dip-and-roll process with a rolling rate of 80%, and then pre-baked at a pre-baking temperature of 40°C and a pre-baking time of 3 minutes, and then dried at 100°C for 3 minutes, and then washed with pure water for 5 times, and dried at 55°C for 7 hours to obtain a radiation-proof fabric. Example 3
[0018] A method for preparing a radiation-proof fabric, the method comprising the following steps: (1) Polyacrylonitrile, triethylenetetramine and N,N-dimethylformamide were mixed in a mass ratio of 1:12:20, stirred and reacted at 90°C for 4 hours, and after the stirring was completed, dichloromethane 30 times the mass of the polyacrylonitrile was added, filtered and washed with ethanol for 3 times, and dried in a vacuum drying oven at a temperature of 80°C and a vacuum degree of 0.08MPa for 12 hours to obtain amino polyacrylonitrile; amino polyacrylonitrile, tetraaldehyde phenylporphyrin, trifluoroacetic acid and N,N-dimethylformamide were mixed in a mass ratio of 1:3:6:60, and vacuum-purged and nitrogen-filled for three cycles at a vacuum degree of 80Pa. Under a nitrogen atmosphere, the temperature was raised to 110°C, stirred and reacted for 48 hours at a stirring speed of 300r / min. After the stirring reaction was completed, dichloromethane in an amount equal to that of N,N-dimethylformamide was added, and dried at 50°C for 6 hours to obtain porphyrin-based polyacrylonitrile; (2) Porphyrin-based polyacrylonitrile, 3-(2-thienyl)-1-propylamine, trifluoroacetic acid and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:4:6:60, and vacuum-purged and nitrogen-purged for three cycles with a vacuum degree of 80 Pa. Under a nitrogen atmosphere, the temperature was raised to 110°C, and the reaction was stirred for 48 hours at a stirring speed of 300 r / min. After the stirring reaction was completed, an equal volume of dichloromethane and N,N-dimethylformamide were added, and the mixture was dried at 50°C for 6 hours to obtain thienyl polyacrylonitrile; (3) Boron nitride and 5 mol / L sodium hydroxide aqueous solution were mixed in a mass volume ratio of 1:15, stirred at 110°C for 10 h, and the stirring speed was 200 r / min. After cooling to room temperature, the mixture was filtered and washed with pure water for 7 times, and dried in a vacuum drying oven at a temperature of 50°C and a vacuum degree of 0.08 MPa for 10 h to obtain hydroxyboron nitride; hydroxyboron nitride, trimethoxy(thiophene-2-yl)silane, and anhydrous ethanol were mixed in a mass ratio of 1:0.5:60, ultrasonicated at 20 kHz for 10 min, stirred at room temperature for 2 h, and the stirring speed was 300 r / min. The mixture was filtered and washed with anhydrous ethanol for 3 times, and dried in a vacuum drying oven at a temperature of 50°C and a vacuum degree of 0.08 MPa for 10 h to obtain thienyl boron nitride; (4) Weigh 2 parts of thienyl boron nitride, 150 parts of N,N-dimethylformamide, 15 parts of thienyl polyacrylonitrile, and 0.5 parts of anhydrous ferric chloride, by mass, mix the thienyl boron nitride and N,N-dimethylformamide, and ultrasonicate at 20 kHz for 30 min. Then, add thienyl polyacrylonitrile and anhydrous ferric chloride in sequence, stir at room temperature for 20 min at a stirring speed of 400 r / min, and ultrasonicate at 20 kHz for 30 min to obtain a spinning solution; (5) The spinning solution is sucked by a syringe, and the spinning solution is squeezed out through a needle. The extruded spinning solution enters a coagulation liquid to obtain a primary fiber. The primary fiber is sequentially subjected to a first mechanical drawing, a second mechanical drawing, a third mechanical drawing and a drawing box to obtain a stretched fiber. Finally, the stretched fiber is collected on a winding roller to obtain a functionalized polyacrylonitrile fiber. The syringe specification is 20 mL, the inner diameter of the needle is 0.5 mm, the extrusion speed is 0.42 mL / min, the coagulation liquid is a mixture of N,N-dimethylformamide and water in a volume ratio of 1:1, the speed of the first drawing roller is 20 r / min, the speed of the second drawing roller is 32 r / min, the speed of the third drawing roller is 36 r / min, the temperature of the drawing box is 115 ° C, and the speed of the winding roller is 38 r / min. The functionalized polyacrylonitrile fiber is twisted, twisted, warped, drawn, and woven into a fabric to obtain a functionalized polyacrylonitrile fabric. (6) 9,10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide and N,N-dimethylformamide were mixed in a mass ratio of 1:30 to obtain a finishing agent 1; thiophene and tetrahydrofuran were mixed in a mass ratio of 1:30 to obtain a finishing agent 2; the functionalized polyacrylonitrile fabric was immersed in the finishing agent 1 and allowed to stand for 2 minutes, and then finished by a dip-and-roll process with a rolling rate of 80%, pre-baked at a pre-baking temperature of 140°C and a pre-baking time of 3 minutes, and then dried at 100°C for 3 minutes, and continued to be immersed in the finishing agent 2, and then anhydrous ferric chloride 0.3 times the mass of thiophene was added, and allowed to stand for 2 minutes, and finished by a dip-and-roll process with a rolling rate of 80%, and then pre-baked at a pre-baking temperature of 40°C and a pre-baking time of 3 minutes, and then dried at 100°C for 3 minutes, and then washed with pure water for 6 times, and dried at 50°C for 6 hours to obtain a radiation-proof fabric.
[0019] Comparative Example 1 The preparation method of the radiation-proof fabric of Comparative Example 1 differs from that of Example 2 in that step (3) is not included and step (4) is modified to weigh 120 parts of N,N-dimethylformamide and 13 parts of thienyl polyacrylonitrile by mass, ultrasonically treat N,N-dimethylformamide at 30 kHz for 35 min, then add thienyl polyacrylonitrile in turn and stir at room temperature for 25 min at a stirring speed of 500 r / min, and ultrasonically defoam at 30 kHz for 35 min to obtain a spinning solution.
[0020] Comparative Example 2 The preparation method of the radiation-proof fabric of Comparative Example 2 is different from that of Example 2 in that step (6) is modified to uniformly mix thiophene and tetrahydrofuran in a mass ratio of 1:25 to obtain finishing agent 2; the functionalized polyacrylonitrile fabric is immersed in finishing agent 2, and then anhydrous ferric chloride in an amount of 0.25 times the mass of thiophene is added, and the fabric is allowed to stand for 2 minutes, and then finished by a one-immersion-one-rolling process with a rolling rate of 80%, and pre-baked at a pre-baking temperature of 40°C for 3 minutes, and then dried at 100°C for 3 minutes, and then washed with pure water 5 times, and dried at 55°C for 7 hours to obtain the radiation-proof fabric.
[0021] Comparative Example 3 The preparation method of the radiation-proof fabric of Comparative Example 3 is different from that of Example 2 in that step (6) is modified to uniformly mix 9,10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide and N,N-dimethylformamide in a mass ratio of 1:25 to obtain a finishing agent 1; the functionalized polyacrylonitrile fabric is immersed in the finishing agent 1 and allowed to stand for 2 minutes, and is finished by a dipping and rolling process with a rolling rate of 80%, and is pre-baked at a pre-baking temperature of 140° C. for 3 minutes, and then dried at 100° C. for 3 minutes, and then washed with pure water 5 times, and dried at 55° C. for 7 hours to obtain the radiation-proof fabric.
[0022] Test Example 1 Flame retardant performance test Test method: The radiation protection fabrics prepared in all comparative examples and embodiments were tested for limiting oxygen index of Examples 1-3 and Comparative Examples 1-3 using intelligent oxygen index determination according to GB / T 5454-1997 "Oxygen Index Method for Textile Combustion Performance Test". The results are shown in Table 1.
[0023] Table 1
[0024] From the comparison of the experimental data of Examples 1-3 and Comparative Examples 1-3 in Table 1, it can be found that the radiation-proof fabric prepared by the present invention has good flame retardant properties.
[0025] By comparison, the limiting oxygen index of Examples 1-3 is greater than that of Comparative Example 2, indicating that the amino polyacrylonitrile and tetraaldehyde phenylporphyrin are reacted to obtain porphyrin-based polyacrylonitrile, and the tetraaldehyde phenylporphyrin is grafted with the amino polyacrylonitrile through the Schiff base reaction. The excess tetrahydroxyaldehyde phenylporphyrin makes the porphyrin-based polyacrylonitrile carry an aldehyde group, and further reacts with 3-(2-thienyl)-1-propylamine to obtain thienyl polyacrylonitrile with thiophene. The Schiff base structure contained in the thienyl polyacrylonitrile can be grafted with a flame retardant through a phosphine hydrogenation reaction in the subsequent finishing process to give the fabric good flame retardant properties.
[0026] Test Example 2 Radiation protection performance test Test method: The radiation protection performance of the radiation protection fabrics prepared in the examples and comparative examples was measured with reference to the standard GB / T 23463-2009 "Protective clothing against microwave radiation", and the test was conducted 10 times in parallel at a test frequency of 300 MHz, and the average value was calculated. The results are shown in Table 2.
[0027] Table 2
[0028] From the comparison of the experimental data of Examples 1-3 and Comparative Examples 1-3 in Table 2, it can be found that the radiation-proof fabric prepared by the present invention has good radiation-proof performance.
[0029] By comparison, the shielding effectiveness of Examples 1-3 is greater than that of Comparative Example 1, indicating that the amino polyacrylonitrile and tetraaldehyde phenylporphyrin are reacted to obtain porphyrin-based polyacrylonitrile, the tetraaldehyde phenylporphyrin is grafted with the amino polyacrylonitrile through the Schiff base reaction, and the hydroxy boron nitride and trimethoxy (thiophene-2-yl) silane are reacted to obtain thienyl boron nitride. Boron nitride is a very good thermal conductive radiation protection material, which can give the fabric good radiation protection performance.
[0030] Test Example 3 Antistatic performance test Test method: Use Mitsubishi MCP-730 resistivity meter and ASP four-probe to test the surface square resistance of the radiation-proof fabrics prepared in the embodiment and comparative example, wherein the working voltage is 0V, the ambient temperature is 20°C, and the relative humidity is 65%; during the measurement, the probe is directly placed on the surface of the fabric, and the charge is applied for 1 minute, and the value is recorded after the reading is stable; each sample is measured at least 5 different positions each time, and the average value is taken. The results are shown in Table 3.
[0031] Table 3
[0032] From the comparison of the experimental data of Examples 1-3 and Comparative Examples 1-3 in Table 3, it can be found that the radiation-proof fabric prepared by the present invention has good electrical conductivity.
[0033] By comparing the square resistance of Examples 1-3, which is smaller than that of Comparative Example 3, it is shown that the amino polyacrylonitrile and tetraaldehyde phenylporphyrin are reacted to obtain porphyrin-based polyacrylonitrile, the tetraaldehyde phenylporphyrin is grafted with the amino polyacrylonitrile through the Schiff base reaction, and the excess tetrahydroxyaldehyde phenylporphyrin makes the porphyrin-based polyacrylonitrile carry aldehyde groups, and then continue to react with 3-(2-thienyl)-1-propylamine to obtain thiophene-containing thiophene-based polyacrylonitrile. The thiophene structure can be used in the process of co-blending electrospinning and post-finishing. The fabric has a polythiophene structure, which gives the fabric good conductive properties; secondly, hydroxy boron nitride and trimethoxy (thiophene-2-yl) silane are reacted to obtain thiophene boron nitride, and the hydroxylated boron nitride and trimethoxy (thiophene-2-yl) silane are coupled to give the boron nitride a thiophene structure. The boron nitride with a thiophene structure and the thiophene-based polyacrylonitrile with a thiophene structure can be cross-linked when blended, and in the post-finishing process, the fabric has a polythiophene structure, which gives the fabric good conductive properties.
[0034] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A radiation-proof fabric, characterized in that: The radiation-proof fabric is prepared by reacting amino polyacrylonitrile and tetraaldehyde phenylporphyrin to obtain porphyrin-based polyacrylonitrile, reacting porphyrin-based polyacrylonitrile and 3-(2-thienyl)-1-propylamine to obtain thienyl polyacrylonitrile; reacting hydroxy boron nitride and trimethoxy(thien-2-yl)silane to obtain thienyl boron nitride; electrostatically spinning thienyl polyacrylonitrile and thienyl boron nitride to obtain functionalized polyacrylonitrile fiber; weaving the functionalized polyacrylonitrile fiber to obtain functionalized polyacrylonitrile fabric, and finishing the functionalized polyacrylonitrile fabric with 9,10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide and thiophene to obtain the radiation-proof fabric.
2. A method for preparing radiation-proof fabric, characterized in that: The method comprises the following preparation steps: (1) Aminated polyacrylonitrile, tetraaldehyde phenylporphyrin, trifluoroacetic acid and N,N-dimethylformamide are mixed uniformly in a mass ratio of 1:2-3:5-6:50-60, and vacuum-purged and nitrogen-purged for three cycles, with a vacuum degree of 80-100 Pa. In a nitrogen atmosphere, the temperature is raised to 110-120° C., and the reaction is stirred for 48-50 hours at a stirring speed of 300-400 r / min. After the stirring reaction is completed, an equal volume of dichloromethane and N,N-dimethylformamide are added, and the mixture is dried at 50-60° C. for 6-8 hours to obtain porphyrin-based polyacrylonitrile; (2) Thienyl polyacrylonitrile, 3-(2-thienyl)-1-propylamine, trifluoroacetic acid and N,N-dimethylformamide are mixed uniformly in a mass ratio of 1:3-4:5-6:50-60, and vacuum-purged and nitrogen-filled for three cycles, with a vacuum degree of 80-100 Pa. In a nitrogen atmosphere, the temperature is raised to 110-120° C., and the mixture is stirred for 48-50 hours at a stirring speed of 300-400 r / min. After the stirring reaction is completed, an equal volume of dichloromethane and N,N-dimethylformamide are added, and the mixture is dried at 50-60° C. for 6-8 hours to obtain thienyl polyacrylonitrile; (3) Mix hydroxyboron nitride, trimethoxy(thiophene-2-yl)silane and anhydrous ethanol in a mass ratio of 1:0.3-0.5:50-60, ultrasonicate at 20-40kHz for 10-20min, stir and react at room temperature for 2-3h at a stirring speed of 300-400r / min, filter and wash with anhydrous ethanol for 3-4 times, and dry in a vacuum drying oven at a temperature of 50-60°C and a vacuum degree of 0.08MPa for 10-12h to obtain thiophene boron nitride; (4) mixing thienyl boron nitride and N,N-dimethylformamide, ultrasonically treating at 20-40 kHz for 30-40 min, then sequentially adding thienyl polyacrylonitrile and anhydrous ferric chloride, stirring at room temperature for 20-30 min at a stirring speed of 400-600 r / min, and ultrasonically defoaming at 20-40 kHz for 30-40 min to obtain a spinning solution; (5) sucking the spinning solution with a syringe, squeezing the spinning solution out through a needle, the extruded spinning solution enters the coagulation liquid to obtain primary fibers, the primary fibers are sequentially subjected to a first mechanical drafting, a second mechanical drafting, a third mechanical drafting and a drafting box to obtain stretched fibers, and finally, the stretched fibers are collected on a winding roller to obtain functionalized polyacrylonitrile fibers, the functionalized polyacrylonitrile fibers are subjected to twisting, fixed twisting, warping, drawing in, and weaving on a machine to obtain fabrics, thereby obtaining functionalized polyacrylonitrile fabrics; (6) Prepare finishing agent 1 and finishing agent 2, immerse the functionalized polyacrylonitrile fabric in finishing agent 1 and let it stand for 2-3 minutes, finish it through a dipping and rolling process with a rolling rate of 80%, pre-dry it at a temperature of 140°C for 3 minutes, and then dry it at 100°C for 3 minutes, continue to immerse it in finishing agent 2, and then add anhydrous ferric chloride, let it stand for 2-3 minutes, finish it through a dipping and rolling process with a rolling rate of 80%, pre-dry it at a temperature of 40°C for 3 minutes, and then dry it at 100°C for 3 minutes, wash it with pure water for 5-6 times, and dry it at 50-60°C for 6-8 hours to obtain radiation-proof fabric.
3. The method for preparing a radiation-proof fabric according to claim 2, characterized in that: The preparation method of the amino polyacrylonitrile in step (1) is to uniformly mix polyacrylonitrile, triethylenetetramine and N,N-dimethylformamide in a mass ratio of 1:8-12:15-20, stir and react at 90-100°C for 4-6h, add dichloromethane 20-30 times the mass of the polyacrylonitrile after stirring, filter and wash with ethanol 3-4 times, and dry in a vacuum drying oven at a temperature of 80°C and a vacuum degree of 0.08MPa for 12-14h to obtain the amino polyacrylonitrile.
4. The method for preparing a radiation-proof fabric according to claim 2, characterized in that: The preparation method of hydroxyboron nitride in step (3) is as follows: boron nitride and 5 mol / L sodium hydroxide aqueous solution are mixed in a mass ratio of 1:10-15, stirred at 110-120°C for 10-12h, and the stirring speed is 200-300r / min. After cooling to room temperature, the mixture is filtered and washed with pure water for 5-7 times, and dried in a vacuum drying oven at a temperature of 50-60°C and a vacuum degree of 0.08MPa for 10-12h to obtain hydroxyboron nitride.
5. The method for preparing a radiation-proof fabric according to claim 2, characterized in that: The weighed amounts of the thienyl boron nitride, N,N-dimethylformamide, thienyl polyacrylonitrile and anhydrous ferric chloride in step (4) are as follows: 1-2 parts by mass of thienyl boron nitride, 100-150 parts by mass of N,N-dimethylformamide, 10-15 parts by mass of thienyl polyacrylonitrile and 0.3-0.5 parts by mass of anhydrous ferric chloride.
6. The method for preparing a radiation-proof fabric according to claim 2, characterized in that: The syringe specification of step (5) is 20mL, the inner diameter of the needle is 0.5mm, the extrusion speed is 0.38-0.42mL / min, the coagulation liquid is prepared by mixing N,N-dimethylformamide and water in a volume ratio of 1:1, the speed of the first stretching roller is 20r / min, the speed of the second stretching roller is 32r / min, the speed of the third stretching roller is 36r / min, the temperature of the stretching box is 115°C, and the speed of the winding roller is 38r / min.
7. The method for preparing a radiation-proof fabric according to claim 2, characterized in that: The preparation method of the finishing agent 1 in step (6) is to mix 9,10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide and N,N-dimethylformamide in a mass ratio of 1:20-30, and the preparation method of the finishing agent 2 is to mix thiophene and tetrahydrofuran in a mass ratio of 1:20-30, and the amount of anhydrous ferric chloride added is 0.2-0.3 times the mass of thiophene.
Citation Information
Patent Citations
Preparation method of novel polyacrylonitrile fiber material
CN109137506A
Modified polypropylene differential fiber, preparation method thereof and non-woven fabric
CN115478335A
Porphyrin metal complex containing Rind-based Schiff base as well as synthesis method and application of porphyrin metal complex
CN118754889A
Organic silicon modified high polymer material as well as preparation method and application thereof
CN118879077A
Cited By
Anti-radiation fabric and preparation method thereof
CN119843496A
